"The Menthol One Is More Friendly": Young Singaporeans' Perspectives on Flavored Cigarettes. (March 2022) - van der Eijk, Yvette; Lin, Lavinia; Gan, Lydia; Teo, Odelia; Subramaniam, Mythily; Lee, Jeong Kyu
Over half of the cigarettes sold in Singapore contain added flavors such as menthol. We conducted nine focus group discussions (n = 46) with young (aged 20-25) current smokers in Singapore to understand the role of flavors in smoking initiation. We found that flavors triggered the curiosity to experiment with tobacco and e-cigarette products and played an important role in the formation of early cigarette preferences. Menthol-flavored cigarettes were the most appealing to participants due to their smoothness and cooling sensation, described as pleasant against Singapore's hot and humid climate. While some participants believed that flavored and nonflavored cigarettes were equally harmful, others believed that flavored variants had a lower nicotine content and were therefore less harmful, or that the added chemicals in flavored cigarettes could result in higher toxicant exposures. Thus, among young people in Singapore, flavors appear to play an important role in smoking initiation and there appear to be various misperceptions regarding their harmfulness.